Decision support system development for cooperative air traffic management - Kharchenko, V. P.; Vasylyev, V. M. (Proceedings of National Aviation University (archive), 2003)
This paper presents the conceptual framework upon which a Decision Support System for conflictdetection and resolution is expected to develop for Cooperative Air Traffic Management. Intent-BasedAdaptive reasoning based on controllability (maneuverability) o f dynamic aircraft model andMultiple-choice Analysis with use o f Controller-Pilot Data Link Communications is investigated